2016
DOI: 10.1134/s0012496616010117
|View full text |Cite
|
Sign up to set email alerts
|

The role of alpha-synuclein in the development of the dopaminergic neurons in the substantia nigra and ventral tegmental area

Abstract: Alpha-synuclein is a presynaptic protein of vertebrates that belongs to the family of synucleins. Normal functions of synucleins remain unknown. Alpha-synuclein is one of the causative factors of the familial and idiopathic forms of Parkinson's disease (PD). The progressive loss of dopaminergic (DA) neurons is characteristic of PD and the most severe damage occurs in the substantia nigra (SN). This leads to an erraticism of the synthesis and synaptic secretion of the neurotransmitters, subsequently resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…And similarly Connor-Robson et al reported that stabilization of the striatal DA level depends on the presence of α-syn and cannot be compensated by other family members. [36] α-syn modulates dopaminergic neuron development, DA reuptake and stabilizes striatal DA level [3537] . 5) α-syn modulates microglial phenotype and neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…And similarly Connor-Robson et al reported that stabilization of the striatal DA level depends on the presence of α-syn and cannot be compensated by other family members. [36] α-syn modulates dopaminergic neuron development, DA reuptake and stabilizes striatal DA level [3537] . 5) α-syn modulates microglial phenotype and neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal levels of the major brain fatty acid docosahexaenoic acid (DHA) decrease with age in rats [40], which is associated with learning and memory deficits [41]. PD is characterized by the progressive loss of dopaminergic neurons, particularly in the substantia nigra, leading to significant dopamine depletion in the striatum, which is responsible for the motor symptoms of PD [42]. The concentration of O3FA decreases in the substantia nigra of patients with PD, whereas the concentration of malondialdehyde, a lipid oxidation marker, increases.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…[ 207 , 208 ]. For example, in Parkinson’s disease, the SNCA gene encoding α-synuclein, a short cytoplasmic protein (140 amino acids in humans), is predominantly synthesized in the nervous system and localized in presynaptic terminals [ 209 , 210 , 211 ]. The most typical histopathological signs of Parkinson’s are the Lewy bodies found in the dopaminergic neurons of substantia nigra and dystrophic neuritis in the tract leading from substantia nigra to the striatum containing aggregates of various proteins [ 212 , 213 ].…”
Section: Problems and Targets In The Treatment Of Neurodegeneative DImentioning
confidence: 99%